a The Relationship Between Health Professionals' Interprofessional Competence and the Speed of Action in Acute Emergency Situations: The Relationship Between Health Professionals' Interprofessional Competence and the Speed of Action in Acute Emergency Situations - Darmawan, Rezky (JURNAL KESMAS DAN GIZI (JKG), 2023)
The Relationship Between Health Professionals' Interprofessional Competence and the Speed of Action in Acute Emergency Situations